2015
DOI: 10.1039/c4an01483a
|View full text |Cite
|
Sign up to set email alerts
|

Propofol detection and quantification in human blood: the promise of feedback controlled, closed-loop anesthesia

Abstract: The performance of a membrane-coated voltammetric sensor for propofol (2,6-diisopropylphenol) has been characterized in long term monitoring experiments using an automated flow analytical system (AFAS) and by analyzing human serum and whole blood samples by standard addition. It is shown that the signal of the membrane-coated electrochemical sensor for propofol is not influenced by the components of the pharmaceutical formulation of propofol (propofol injectable emulsion). The current values recorded with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
(35 reference statements)
1
30
0
Order By: Relevance
“…This problem is usually solved by adding a PVC membrane on the WE surface, as in [20]. In any case, data compare quite well with those published in literature on the same redox reactions [21], [22], [23].…”
Section: B Electrochemical Measurementssupporting
confidence: 71%
“…This problem is usually solved by adding a PVC membrane on the WE surface, as in [20]. In any case, data compare quite well with those published in literature on the same redox reactions [21], [22], [23].…”
Section: B Electrochemical Measurementssupporting
confidence: 71%
“…The root mean squared error of the output of the system with respect to the targeted concentration (RMSE target) yielded a higher average error from all the experiments of 25.10% ± 11.49%. This value is higher than the ferrocene methanol experiments in part due to the membrane coating of the glassy-carbon sensor [12]. The average steady-state error is in the same range of the ferrocene methanol experiments, 5.19% ± 3.91%.…”
Section: Discussionmentioning
confidence: 68%
“…To achieve actual control instead of "targeted" control, the concentration of propofol has to be measured continuously during total intravenous anesthesia (TIVA). Recently, our group has developed an electrochemical sensor for continuous monitoring of propofol in complex biological solutions, including whole blood [9][10][11][12]. It has been shown that the performance characteristics [13] of the propofol sensor (precision, accuracy, response time, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the conclusions of our model calculations on the accuracy of the determination of diffusion coefficients in highly viscous media from the scan rate dependence of LSVs the diffusion coefficient of ferrocene was determined in 2‐nitrophenyl octylether (o‐NPOE) using different sizes of electrodes. o‐NPOE is a commonly used plasticizer of polyvinyl chloride (PVC)‐based ion‐selective membranes and membranes used to modify the response of voltammetric working electrodes . To determine the diffusion coefficient of ferrocene a series of linear‐sweep voltammograms were recorded with different sizes of electrodes (10, 25, 76, and, 125 μm diameters) and scan rates (100, 50, 10, and 5 mV/s which correspond to p‐values between 0.25 and 13).…”
Section: Resultsmentioning
confidence: 99%
“…Ferrocene (98 %) and ferrocenecarboxylic acid, FcCOOH (97 %) were purchased from Sigma-Aldrich. Tetrabuty-lammonium perchlorate, 2-nitrophenyl octyl ether (oN-POE) and PVC (high molecular weight) were products of Sigma-Aldrich while tetradodecylammonium tetrakis (pentafluorophenyl) borate, TDDA-TPFPhB was prepared by metathesis from tetradodecylammonium chloride (Sigma-Aldrich) and potassium tetrakis (pentafluorophenyl) borate (Boulder Scientific) as described previously [1][2][3]. Tetrabutylammonium perchlorate was recrystallized two times from ethyl acetate before use, and all other reagents were used as received without additional purification.…”
Section: Reagents and Membranesmentioning
confidence: 99%